The External-Relational Shift in Faith (Pistis) in New Testament Research: Romans 1 as Gospel-Allegiance Test Case. (February 2020) - Bates, Matthew W.
Evidence is marshalled for a recent 'external-relational shift' in scholarly understandings of pistis (traditionally translated 'faith') among New Testament scholars and historians of early Christianity and its social world. There is a movement away from predominantly personal existential accounts of pistis toward those that are relational and outwardly manifest. 'Faith' ( pistis ) is predominantly a way of life characterized by fidelity or loyalty which is outwardly expressed in relationships. Beyond the New Perspective on Paul, which is an obvious factor, four streams are feeding this shift: (1) the pistis Christou debate, (2) increased appreciation of ancient social and cultural norms, (3) advances in linguistics, and (4) an emphasis on the gospel as a royal proclamation. To show why the external-relational shift matters theologically, Paul's use of pistis in Romans 1 is explored along external-relational lines.